Microbial Response to the MC-252 Oil and Corexit 9500 in the Gulf of Mexico - Chakraborty, Romy; Borglin, Sharon E.; Dubinsky, Eric A.; Andersen, Gary L.; Hazen, Terry C. (Frontiers in Microbiology, 2012)
The Deepwater Horizon spill released over 4.1 million barrels of crude oil into the Gulf of Mexico. In an effort to mitigate large oil slicks, the dispersant Corexit 9500 was sprayed onto surface slicks and injected directly at the wellhead at water depth of 1,500 meters. Several research groups were involved in investigating the fate of the MC-252 oil using newly advanced molecular tools to elucidate microbial interactions with oil, gases and dispersant. Presented here is a comprehensive overview of the ecogenomics of microbial degradation of MC-252 oil and gases in the water column and shorelines and some insight into the fate of the dispersant Corexit 9500 that was added to aid in oil dispersion process. We also present data that show the dispersant was not toxic to the indigenous microbes at concentrations added, and several bacterial species were able to degrade the various components of Corexit 9500.